Health education, communication and safety culture in diagnostic imaging: a narrative review of up-to-date guidelines - Tołkacz, Aleksandra; Kwiatkowska, Aleksandra; Gewald, Maja; Król, Adrianna; Sobczak, Julia; Kosikowska, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction. Advances in diagnostic imaging have increased precision and patient access, but also generated new safety challenges regarding ionizing radiation, magnetic field hazards, and procedural complexity. Technological optimization is fundamental, although real-world safety outcomes are heavily influenced by organizational and patient-related factors. Aim. This narrative review synthesizes up-to-date international guidelines and literature (published between 2015 and 2026), focusing on health education and clinical communication as vital yet underutilized contributors to patient safety. A brief description of the state of knowledge. Radiation protection remains anchored in the ALARA principle. However, the importance of automated dose tracking systems and AI-assisted image reconstruction is growing. Technology alone cannot completely eliminate all risks; motion artefacts, repeat scans, and workflow delays often result from scan-related anxiety and limited health literacy. Evidence points to the effectiveness of structured patient preparation, particularly Virtual Reality (VR) in pediatrics, to reduce sedation requirements and improve cooperation. Broader safety discussions now include a “Just Culture” approach, burnout prevention, and “Green Radiology” practices. Summary. Patient safety in diagnostic imaging is a multidimensional issue. Enhancing it requires combining technological optimization with effective health education. Developing communication competencies among radiological personnel via digital technologies, including artificial intelligence, further supports safe practice. To maintain a patient-centered safety culture that evolves as technology changes, embedding health literacy and effective communication strategies into medical curricula is recommended.